2003
DOI: 10.1002/neu.10257
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in avian song control circuits do not cause seasonal changes in song discrimination in song sparrows

Abstract: In seasonally breeding songbirds, brain nuclei of the song control system that act in song perception change in size between seasons. It has been hypothesized that seasonal regression of song nuclei may impair song discrimination. We tested this hypothesis in song sparrows (Melospiza melodia), a species in which males share song types with neighbors and must discriminate between similar songs in territorial interactions. We predicted that song sparrows with regressed song systems would have greater difficulty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Song sparrows do not hoard food, and consistent with this observation, HP size does not vary seasonally in song sparrows (Lee et al, 2001). The NCM may function in song perception (Mello et al, 1992), which does not appear to vary seasonally in captive song sparrows (Reeves et al, 2001). Based on the above information, we hypothesized that androgen-metabolizing enzymes in the HP and NCM would not vary seasonally, making them useful "control" regions.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Song sparrows do not hoard food, and consistent with this observation, HP size does not vary seasonally in song sparrows (Lee et al, 2001). The NCM may function in song perception (Mello et al, 1992), which does not appear to vary seasonally in captive song sparrows (Reeves et al, 2001). Based on the above information, we hypothesized that androgen-metabolizing enzymes in the HP and NCM would not vary seasonally, making them useful "control" regions.…”
supporting
confidence: 56%
“…It is possible that hearing song up-regulates enzymes in NCM or, alternatively, that seasonal changes of enzymes in NCM produce changes in song perceptual abilities (Fusani et al, 2000). Song perception in captive male song sparrows does not appear to vary seasonally (Reeves et al, 2001), but neither wild nor molting birds have been examined. Local implants of aromatase inhibitors and/or estradiol to NCM would be an informative next step.…”
Section: Seasonal Changesmentioning
confidence: 98%
“…Male and female white-throated sparrows sing year-round (see Falls and Kopachena, 1994), and their auditory systems are presumably tuned to conspecific song regardless of season and sex steroid level. Using operant conditioning techniques, Reeves et al (2003) demonstrated that seasonal changes in day length and plasma levels of sex steroids do not affect the ability to discriminate between similar conspecific songs in another Emberizid, the song sparrow. The results we report here are not likely to indicate changes in discrimination ability or hearing sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, returning (ASY) male juncos may recognize the vocal behavior of some neighbors based on previous learning experience, resulting in their having less new auditory information to learn than SY males establishing boundaries with neighbors for the first time. One study that assessed the ability of Song Sparrows (Melospiza melodia) to discriminate between very similar conspecific songs, however, found no deficit in this ability in short photoperiod-exposed birds with regressed SCRs compared to long photoperiod-exposed birds with exogenous T and large SCRs, suggesting that large SCRs are not necessary for this task [Reeves et al, 2003].…”
Section: Age Differences In Brain and Behaviormentioning
confidence: 99%